Appropriate cultural practices for growing wheat using expert system - Islam, S.N.; Dhar, Shiva; Sharma, Kirti (Annals of Agricultural Research, 2016)
Expert System on Wheat Crop Management has been developed by the scientists of IASRI in collaboration with two premier institutions doing research on wheat namely DWR, Karnal and IARI, New Delhi to deliver the package of practices for wheat production to the farmers. The system holds a collection of general principles that are potentially applied to solve a problem related to wheat crop management and extends large information to the wheat-growing farmers. The system works as an information bank for wheat growing farmers that can help them in better crop management in order to enhance productivity and production of wheat in India. The system is available at the URL http://www.iasri.res.in/expert .